2020
DOI: 10.1038/s10038-020-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes on pharmacogenetics among pediatricians

Abstract: Increasing enthusiasm for clinical pharmacogenetic testing and the availability of pharmacogenetic-based guidelines indicate that pediatricians will increasingly be expected to interpret and apply pharmacogenetic test results into medical care. Previous studies have identified a lack of knowledge on pharmacogenetics across many physician specialties; however, this has not been systematically assessed among pediatricians. To evaluate pediatrician knowledge, attitude, and educational interest in pharmacogenetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 31 publications
(45 reference statements)
0
53
0
Order By: Relevance
“…This survey of primary care clinicians revealed the current attitudes and interest of this population towards PGx, experience with PGx testing, and likelihood of a clinician to consult a PGx‐trained pharmacist about test results in this setting. The knowledge and perception questions of the survey revealed that less than half of responding clinicians perceived PGx testing as important for predicting adverse effects or efficacy in their clinics, which is lower than reported in previous surveys 7,17,18 . A recent survey of clinicians in Europe reported 84% of respondents found PGx relevant to their practice; however, this was a population of clinicians whose clinic sites had previously been chosen to implement a PGx educational program 17 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This survey of primary care clinicians revealed the current attitudes and interest of this population towards PGx, experience with PGx testing, and likelihood of a clinician to consult a PGx‐trained pharmacist about test results in this setting. The knowledge and perception questions of the survey revealed that less than half of responding clinicians perceived PGx testing as important for predicting adverse effects or efficacy in their clinics, which is lower than reported in previous surveys 7,17,18 . A recent survey of clinicians in Europe reported 84% of respondents found PGx relevant to their practice; however, this was a population of clinicians whose clinic sites had previously been chosen to implement a PGx educational program 17 .…”
Section: Discussionmentioning
confidence: 77%
“…A recent survey of clinicians in Europe reported 84% of respondents found PGx relevant to their practice; however, this was a population of clinicians whose clinic sites had previously been chosen to implement a PGx educational program 17 . Similarly, a survey of Japanese and American pediatricians reported that greater than 80% of respondents found PGx valuable for improving the safety and efficacy of medications, though less than 10% of this population rated themselves as familiar with PGx 18 . More consistent with our survey results, in a cohort of Canadian family medicine physicians, 43% agreed that learning about implications of genetic testing was relevant to patient care in their clinics 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this survey endorsed the interest in education to equip pediatric clinicians with the skills to implement PGx. 11 However, the current guidelines for interpreting and implementing PGx are based largely on adult data, and it is unclear how well they apply to the care of children and adolescents. Thus, PGx testing in pediatrics is most often reactive, and it is not clear which pediatric patients may benefit most from reactive testing with regard to their current clinical care or pre-emptive testing to guide future drug therapy.…”
Section: Pharmacogenetic Testing In Childrenmentioning
confidence: 99%
“…These perceptions are evolving with the breakneck speed of information regarding pharmacogenomics. Studies about the perceptions and barriers five years ago are going to be significantly different than those surveyed in 2020 [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%